A study on the microstructure and properties of brazing joint for Cr18-Ni8 steel using a BNi7+9%Cu mixed filler metal. (May 2018) - Shi, Haichuan; Yu, Zhishui; Cho, JongRae
Abstract: Vacuum brazing of Cr18-Ni8 steel was performed using the BNi7+9%Cu mixed filler metal at the different brazing temperature. Microstructure, microhardness and shear strength were investigated by means of scanning electron microscopy (SEM), energy-dispersive spectroscopy (EDS), hardness tester and AG-25TA electronic universal material testing machine. The results indicated that the brazed region was divided into isothermal solidification zone (ISZ) and athermal solidification zone (ASZ). The γ-Ni (Cr, Fe, Cu) solid solution was formed in the ISZ, and its thickness would increase as brazing temperature increased. On the other hand, the generated microstructure was different by the change of chemical composition in the ASZ and its microhardness would increase as the brazing temperature increased. Elemental distribution indicated that Ni and Cu gradually gathered on both sides of the brazed joints as brazing temperature increased, while P and Cr were concentrated in the middle. In addition, the bonding behaviors of brazed joint was also illustrated based on the elemental distribution and microstructure distribution of brazed joint. Finally, an excellent brazing joint of Cr18-Ni8 steel was obtained at 980 °C for 30 min s and its shear strength was as high as 144 MPa. Highlights: A new type of BNi7+9%Cu mixed filler metal was researched in this study. The microscopic features of brazed joints formed under different brazing temperatures were elaborated. Bonding behaviors of brazed joints were presented in detailed diagraph and words. The shear strength of brazed joints and the reason for the fracture were evaluated and analyzed.